Intelligent control algorithms for posture and height control of four-leg hydraulic supports - Yihui Pang; Yaoyu Shi (Scientific Reports)
Abstract To address limitations of traditional inclinometers and height sensors in determining the posture and support height of hydraulic supports in coal mining, we propose a novel method predicated on travel measurements of the leg and tail beam cylinders. This method calculates the posture and height of hydraulic supports in mechanized mining. By conducting meticulous kinematic analysis of the hydraulic supports, a skeleton model of the main structural parameters of the hydraulic support was constructed. This approach transforms the traditional geometric relationship solutions of the main structure of the hydraulic supports into solutions based on the coordinate relationships of the main hinge points of the support, resulting in a mathematical expression for solving the support posture and height of the hydraulic supports. Meticulous algorithms for solving the support posture and height of hydraulic supports were developed based on the Newton–Raphson method, secant method, and Broyden’s method. The robustness, stability, calculation accuracy, and speed of these algorithms have been verified through analysis using the skeleton model and field measurement methods. The influence of initial coordinate parameters on the calculation results has been analyzed, and it was determined that the solution method based on the Newton–Raphson method has better robustness, stability, and calculation speed. The results of the research provide a theoretical foundation and technical support for precise, rapid control and intelligent management of hydraulic supports, effectively advancing the development of intelligent control systems for mining equipment.